A glimpse on passive control using porous media for incompressible aerodynamics. (1st January 2014) - Bruneau, Charles-Henri; Creusé, Emmanuel; Gilliéron, Patrick; Mortazavi, Iraj
The control of two-dimensional flows around bluff-bodies is achieved using porous devices added to some parts of the body. The bodies can be square or circular cylinders as well as a moving Ahmed body on the top of a road. The flow in different media is modelled by means of the penalisation method. A good choice of the location of the porous interfaces yields a significant improvement of the aerodynamic quantities. Finally, a coupled active/passive control is presented in order to achieve a better drag reduction. A glimpse on passive control using porous media.